The development of inflectional morphology in l2 acquisition: a cross-linguistic analysis The development of inflectional morphology in l2 acquisition: a cross-linguistic analysis - M. Rafael Salaberry (Ilha do Desterro, 2008)
The development of several grammatical features among adult L2 (second language) learners (e.g., inflectional morphology) may be guided by strictly general cognitive processes (e.g., Bley-Vroman, 1989; Schmidt, 1990). For instance, Flynn and Manuel (1991) argue that general learning mechanisms — non-modular and unrelated to Universal Grammar (UG) — may determine the acquisition of “
peripheral" language phenomena:

Many studies that argue for differences between the child
L1 learner and the adult L2 learner in ultimate attainment
focus on surface aspects of L2 language knowledge connected
to "periphery" of language knowledge (e.g., lexical or
language-specific agreement phenomena) rather than to the
more abstract subsystems of principles and rules of UG.

Similarly, Schwartz (1993, p. 159) claims that it is not arranted to extend the UG argument for the acquisition of syntax "to the other domains of the grammar, in particular to the lexicon and morphology (e.g., paradigms of inflection)."
Schwartz states further that inflectional endings are among the most difficult features of nonnative languages for adult learners: "highest amount of variability and lowest degree of
success." Schwartz (1993, p. 160) speculates that "the syntax (being built on the basis of primary linguistic data) continues to grow but the morphology seems to lag behind: learned linguistic knowledge, in this case inflectional verbal morphology, just cannot feed into the grammar." The development of several grammatical features among adult L2 (second language) learners (e.g., inflectional morphology) may be guided by strictly general cognitive processes (e.g., Bley-Vroman, 1989; Schmidt, 1990). For instance, Flynn and Manuel (1991) argue that general learning mechanisms — non-modular and unrelated to Universal Grammar (UG) — may determine the acquisition of “
peripheral" language phenomena:

Many studies that argue for differences between the child
L1 learner and the adult L2 learner in ultimate attainment
focus on surface aspects of L2 language knowledge connected
to "periphery" of language knowledge (e.g., lexical or
language-specific agreement phenomena) rather than to the
more abstract subsystems of principles and rules of UG.

Similarly, Schwartz (1993, p. 159) claims that it is not arranted to extend the UG argument for the acquisition of syntax "to the other domains of the grammar, in particular to the lexicon and morphology (e.g., paradigms of inflection)."
Schwartz states further that inflectional endings are among the most difficult features of nonnative languages for adult learners: "highest amount of variability and lowest degree of
success." Schwartz (1993, p. 160) speculates that "the syntax (being built on the basis of primary linguistic data) continues to grow but the morphology seems to lag behind: learned linguistic knowledge, in this case inflectional verbal morphology, just cannot feed into the grammar."